Hydrogen peroxide mediates triclosan-induced inhibition of root growth in wheat seedlings. (December 2018) - Sun, Chengliang; Dudley, Stacia; McGinnis, Michelle; Gan, Jay
Abstract: Triclosan, an extensively used antimicrobial agent, enters agroecosystems when sewage sludge and reclaimed water are applied to agricultural fields, and may trigger a series of plant physiological and biochemical responses. However, few studies have investigated the mechanism by which plant development is affected by triclosan. Here, microscopic, pharmacological and biochemical analyses, and histochemical dye staining were used to explore the effects of triclosan on root growth in wheat plants. Exposure to triclosan inhibited root elongation, and significantly triggered hydrogen peroxide (H2 O2 ) production and lipid peroxidation in wheat roots. The inhibition of root growth by triclosan was reversed by dimethylthiourea, a H2 O2 scavenger, indicating that alterations of endogenous H2 O2 concentrations in root cells were likely linked to triclosan-induced root growth inhibition. The addition of butylated hydroxyanisole, a lipophilic antioxidant, during triclosan treatment completely prevented the increase of lipid peroxidation, but did not alleviate triclosan-induced reduction of root growth. In triclosan-treated wheat roots, the level of indole-3-acetic acid decreased by 68.3%, while the contents of two indole-3-acetic acid oxidative metabolites, indole-3-aldehyde and indole-3-carboxylic acid, increased by 71.3% and 314.4%, respectively. Moreover, the oxidation of auxin induced by triclosan in wheat roots was prevented by dimethylthiourea. These results together suggested that the triclosan-enhanced production of H2 O2 induced auxin oxidation, thus leading to the suppression of root growth. Findings of this study improve our mechanistic understanding on how antimicrobial agents such as triclosan affect plant root growth. Graphical abstract: Image 1 Highlights: Triclosan led to a pronounced inhibition of root elongation in wheat seedlings. Eliminating H2 O2 alleviated triclosan-induced inhibition of root growth. H2 O2 likely exerted its toxicity by disrupting the auxin signaling pathway.